λ-model with competing Potts interactions on Cayley tree of order 2 - Mukhamedov, Farrukh; Pah, Chin Hee; Jamil, Hakim (American Institute of Physics Inc., 2018)
In this paper, we consider the λ-model on Cayley tree for order two with Potts competing nearest-neighbor and prolonged next-nearest neighbor-interactions. We described the construction of the Gibbs measure for the considered model. We proved the existence of the translation-invariant limiting Gibbs measures for the model.